2016
DOI: 10.2495/air160091
|View full text |Cite
|
Sign up to set email alerts
|

PM10emissions due to storage in coal piles in a mining industrial area

Abstract: Fugitive material has been identified as the main source of air pollution, especially total suspended particulate (TSP) and particulate matter less than 10 micrometers (PM 10 ) in open pit mining. The aim of this research was to estimate the concentration of PM 10 and measure the impact of coal piles on nearby populations. The sources under consideration are three different areas for coal storing. All three areas are distributed along the mine with 14 piles with a total capacity of 3.2 Mton. Emissions were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(4 reference statements)
0
4
0
1
Order By: Relevance
“…To identify possible emission sources at the sampling sites, all maps figures show spatial location of pits, disposal, and storing areas inside the mining areas. Coal storage piles (A1, A2, and A3) were identified from a previous report (Rojano et al, 2016). A1 and A2 are located in the north of the mining zone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify possible emission sources at the sampling sites, all maps figures show spatial location of pits, disposal, and storing areas inside the mining areas. Coal storage piles (A1, A2, and A3) were identified from a previous report (Rojano et al, 2016). A1 and A2 are located in the north of the mining zone.…”
Section: Resultsmentioning
confidence: 99%
“…To locate the possible emission source responsible for high EF values in the sampling sites, we decided to perform an identification of pits, disposal and storing areas inside the mining areas. In a previous report by Rojano et al (2016), were identified three areas for coal storage A1, A2, and A3. We only considered A1 and A3, as they were located near our sampling sites.…”
Section: Demographic Characteristics Groupmentioning
confidence: 99%
“…The highest contribution came from non-paved roads, which is similar to previous studies. Huertas et al [14,38,39] all showed that unpaved roads were the primary source of emissions, with PM 2.5 emissions accounting for 78.4%, 34%, and 60% of the total emissions, respectively, followed by transmission, loading and unloading, wind erosion, and other activities. The second major contribution source in this study was wind erosion on the surface of the coal piles.…”
Section: Pm 25 Emission Inventory Calculation and Spatial Distributionmentioning
confidence: 99%
“…La Guajira es de clima cálido catalogada como la zona más seca de Colombia. La Tabla 1 presenta una descripción de los promedios, desviaciones, valores máximos y mínimos de los parámetros meteorológicos entre enero y junio de 2012 (Rojano et al, 2016).…”
Section: Metodologíaunclassified